Five Years of Islamic Financial Literacy Research in Indonesia in SINTA Indexed Journals: A Bibliography Study - Destya Dwi Putri Andaru; Aurel Alvira Varadita; Shintiya Nailul Rohmah; Sistifanie Putri Handayani; Sabrina Adzani Putri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study aims to determine and discuss the development of research on the influence of Islamic financial literacy from 2020 to 2024 using scientific journals indexed by SINTA (Science and Technology Index) 1,2,3,4,5 and 6. The research method used in this study is the Literature review bibliography method. This study found the fact that the development of research on Islamic financial literacy is still not stable enough, as evidenced by the increase and decrease in each year which is less consistent. The method widely used by researchers in this research is the quantitative method. Most of the articles in this study were published in journals indexed by SINTA 4 and no related articles were found in journals indexed by SINTA 1. This study shows the development of Islamic financial literacy in Indonesia using the bibliographic analysis method, by comparing articles published in journals indexed 1,2,3,4,5 and 6 during the last five years, namely 2020-2024 which have never been studied by other researchers. Keywords: Financial literacy, Sharia, Islamic Finance, Indonesia, Bibliography.